Sutureless versus Stented Bioprostheses for Aortic Valve Replacement: The Randomized PERSIST-AVR Study Design - Lorusso, Roberto; Folliguet, Thierry; Shrestha, Malakh; Meuris, Bart; Kappetein, Arie Pieter; Roselli, Eric; Klersy, Catherine; Nozza, Michele; Verhees, Luc; Larracas, Cristina; Goisis, Giovanni; Fischlein, Theodor (The Thoracic and Cardiovascular Surgeon, 2020)
Introduction Sutureless biological valves for surgical aortic valve replacement (SAVR), characterized by the absence of anchoring sutures at the aortic annulus, are gaining popularity because of ease and reproducibility of implant, shorter operating times, and enhancement of minimally invasive approaches. The stentless configuration of the sutureless valve was designed to achieve optimal hemodynamic performance.Materials and Methods PERSIST-AVR (PERceval Sutureless Implant versus STandard Aortic Valve Replacement) is a prospective, randomized, adaptive, open-label, international, postmarket trial (NCT02673697). The primary objective of the trial is to assess the safety and efficacy of the Perceval (LivaNova, London, UK) sutureless bioprosthesis among patients undergoing SAVR in the presence of severe aortic stenosis to demonstrate the noninferiority of Perceval as compared with standard sutured stented bioprosthetic aortic valve as an isolated procedure or combined with coronary artery bypass grafting. Sample size will be determined adaptively through interim analyses performed by an Independent Statistical Unit till a maximum of 1,234 patients, enrolled at ∼60 sites in countries where the device is commercially available. Patients will be followed up for 5 years after implant. The primary end point is the number of patients free from major adverse cardiac and cerebrovascular-related events at 1 year. Additional secondary outcomes will be assessed up to 5 years.Discussion PERSIST-AVR is the first prospective, randomized study comparing in-hospital and postdischarge outcomes in a robust population of patients undergoing SAVR with either the Perceval sutureless bioprosthesis or a conventional sutured stented bioprosthesis up to 5 years.
Keywords: sutureless; randomized trial; aortic stenosis; aortic valve replacement; study design; stented bioprostheses